Targeted overexpression of prostacyclin synthase inhibits lung tumor progression by recruiting CD4+ T lymphocytes in tumors that express MHC class II. (4th May 2018) - Li, Howard Y.; McSharry, Maria; Walker, Deandra; Johnson, Amber; Kwak, Jeff; Bullock, Bonnie; Neuwelt, Alexander; Poczobutt, Joanna M.; Sippel, Trisha R.; Keith, Robert L.; Weiser-Evans, Mary C. M.; Clambey, Eric; et al.
ABSTRACT: Lung-specific overexpression of prostacyclin synthase (PGIS) decreases tumor initiation in murine lung cancer models. Prostacyclin analogs prevent lung tumor formation in mice and reverse bronchial dysplasia in former smokers. However, the effect of prostacyclin on lung cancer progression has not been well studied. We investigated the effects of pulmonary PGIS overexpression in an orthotopic immunocompetent mouse model of lung cancer using two murine lung cancer cell lines. Pulmonary PGIS overexpression significantly inhibited CMT167 lung tumor growth, increased CXCL9 expression, and increased CD4+ tumor-infiltrating lymphocytes. Immunodepletion of CD4+ T cells abolished the inhibitory effect of pulmonary PGIS overexpression on CMT167 lung tumor growth. In contrast, pulmonary PGIS overexpression failed to inhibit growth of a second murine lung cancer cell line, Lewis Lung Carcinoma (LLC) cells, and failed to increase CXCL9 expression or CD4+ T lymphocytes in LLC lung tumors. Transcriptome profiling of CMT167 cells and LLC cells recovered from tumor-bearing mice demonstrated that in vivo, CMT167 cells but not LLC cells express MHC class II genes and cofactors necessary for MHC class II processing and presentation. These data demonstrate that prostacyclin can inhibit lung cancer progression and suggest that prostacyclin analogs may serve as novel immunomodulatory agents in a subset of lung cancer patients. Moreover, expression of MHC Class II by lung cancer cells may represent a biomarker for response to prostacyclin.